2013
DOI: 10.1186/1687-6180-2013-172
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of non-mass-enhancing lesions in breast MRI based on morphological, kinetic, and spatio-temporal moments and joint segmentation-motion compensation technique

Abstract: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) represents an established method for the detection and diagnosis of breast lesions. While mass-like enhancing lesions can be easily categorized according to the Breast Imaging Reporting and Data System (BI-RADS) MRI lexicon, a majority of diagnostically challenging lesions, the so called non-mass-like enhancing lesions, remain both qualitatively as well as quantitatively difficult to analyze. Thus, the evaluation of kinetic and/or morphological cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Morphological criteria have also been identified as valuable diagnostic tools. Recently, combinations of different dynamic and morphological characteristics have been reported that can reach diagnostic sensitivities up to 97% and specificities up to 76.5% [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological criteria have also been identified as valuable diagnostic tools. Recently, combinations of different dynamic and morphological characteristics have been reported that can reach diagnostic sensitivities up to 97% and specificities up to 76.5% [21].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological criteria have also been identified as valuable diagnostic tools. Recently, combinations of different dynamic and morphological characteristics have been reported that can reach diagnostic sensitivities up to 97% and specificities up to 76.5% [21].In our study we combined both morphologic and dynamic parameters and its modification into BI-RADS category for lesion classification. The sensitivity of MRI examinations was 98.6% while the specificity was78.8%, this was attributed to the small number of the benign lesions, representing 7 (19.4%) out of 36 examined lesions.…”
mentioning
confidence: 99%
“…As per ACR BIRADS LEXICON, there are certain morphological and dynamic contrast enhancement characteristics for assessing lesions on MRI. Combinations of different dynamic and morphological characteristics have been reported that can reach diagnostic sensitivities up to 97% and specificities up to 76.5% [13]. In our study we combined both morphologic and dynamic parameters and its modification into BIRADS category for lesion classification.…”
Section: Dynamic Contrast Mrimentioning
confidence: 99%
“…Also semi-automatic lesion extraction is performed by threshold based segmentation. Hoffmann et al [8] proposed a modification for the segmentation algorithm by Chan and Vese [2]. As comparison algorithm this method is included in our proposed workflow.…”
Section: Related Workmentioning
confidence: 99%
“…By stopping the curve the boundary of the objects is determined. Here, the following modifications proposed by Hoffmann [8] are applied: The contour to be found by the algorithm is set to a three dimensional function in order to evolve a three dimensional segmentation. The segmentation function is modified to achieve a smoother transition of the contour of the lesions which is defined by the newly introduced parameter α.…”
Section: Workflow For Segmentation and Kinetic Analysismentioning
confidence: 99%